Stašo Forenbaher (ed.): A Connecting Sea : Maritime Interaction in Adriatic Prehistory - Tomas, Helena (Array, 2011)
As the title clearly reveals, this is a review of S. Forenbaher (ed.): A Connecting Sea : Maritime Interaction in Adriatic Prehistory (BAR IS 2037, 2009. All chapters are presented briefly, and an overall evaluation of the volume is given.